Updates on the management of Multiple Myeloma: Guidelines by the Hematology and Bone Marrow Transplant Unit at Hospital Universitário Walter Cantídio - Parente Filho, Sérgio; Souza, Jacqueline Holanda de Souza; Rocha, Germana Franck de Souza Bastos; Vasconcelos, João Paulo; Barroso, Karine Sampaio Nunes; Araújo, Beatriz Stella Gomes de Souza Pitombeira; Gurgel, Livia Andrade; Alencar, Rafael da Nóbrega de; Castelo, Lucas Freire; Duarte, Fernando Barroso (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Multiple Myeloma (MM) is a mature hematological neoplasm characterized by histological infiltration (bone marrow and/or extramedullary plasmacytomas) by clonal plasma cells and the presence of one or more defining events, including anemia, renal impairment, osteolytic lesions, and hypercalcemia. The management of MM has drammaticaly evolved over the past few years. However, new drugs are not available in the Brazilian public health service and treatment is still a challenge, especially in the relapsed/refractory setting. We herein summarize the updates in MM management and make recommendations for care in an optimal scenario and in the Brazilian public health service.